Bio-foam: Albumen (Egg Whites) as an Eco-friendly Foaming Agent for Alternative Polyethylene Foam Packaging - Rivera, Carlos Miguel G (Animo Repository, 2023)
Bio-foam, a foam material derived from natural sources, is environmentally friendly and biodegradable. The primary objective of this study is to develop a biodegradable packaging foam using egg white as a foaming agent, aiming to assess its potential as a substitute for polyethylene foam, known for its environmental harm and slow decomposition. The exploration of environmentally friendly alternatives to detrimental materials like polyethylene foam is of paramount importance in mitigating environmental damage, conserving resources, and advancing sustainability. The study employs experimental and quantitative methodologies to compare bio-foam with polyethylene foam. Bio-foam is formulated from gelatin, glycerin, eggshells, and egg whites, and the process involves ingredient mixing, mold pouring, and drying over 5 to 7 days. Subsequently, water absorption, compressibility, and biodegradability tests are conducted on the obtained bio-foam. The water absorption test reveals that the foamy stage exhibits the lowest absorption rate of 9.71% after one minute of immersion. In the biodegradability test, the stiff peak stage demonstrates the highest rate of biodegradability, reaching 21.48% after five days of burial. Additionally, the compression test demonstrates that the stiff peak stage exhibits the highest resistance to pressure, measuring 0.366N/m². Through comparative analysis with polyethylene foam, the study concludes that bio-foam outperforms it in both compressibility and biodegradability. Therefore, it is inferred that albumen-based bio-foam shows potential as a possible substitute for polyethylene foam in packaging applications.